'Pre‐Pack Administration Sale: a Case of Sub Rosa Debt Restructuring'. Issue 2 (15th March 2016) - Wijaya, Anthony
Abstract: Under the UK insolvency regime, debt restructuring is ordinarily achievable via a voluntary arrangement, a scheme of arrangement ("scheme") or a combination of a scheme with administration.1 However, recently, there has been a growing development of companies using pre‐pack administration sale ("pre‐pack sale") to effect a debt restructuring under the moniker of a sale of the assets of the company. This article argues that this development poses a genuine danger for the creditors and in particular the junior creditors2 because such transactions side‐step the protections afforded to the junior creditors in a debt restructuring, particularly a scheme. This article posits that such pre‐pack sales are essentially a sub rosa debt restructuring.3 Against this backdrop, this article proposes for the use of an ex ante judicial regulatory strategy through the application of the Re Tea Corporation principle to better protect the interest of the junior creditors.4 Copyright © 2016 INSOL International and John Wiley & Sons, Ltd. Copyright © 2016 INSOL International and John Wiley & Sons, Ltd